Migrating Methods in a Pandemic: Virtual Participatory Video with Migrants in Hong Kong. (25th June 2022) - Ham, Julie; Lin, Vivian W; Sunuwar, Merina
Can methods travel the way migrants do? We reflect on this question through the development of what we call 'virtual participatory video' or the delivery of participatory video methods for migrant domestic workers and asylum-seekers in Hong Kong – transnationally, online and over Zoom during the pandemic in 2020. The pandemic realities that we grappled with as migration studies scholars and participatory video practitioners reflect realities that working-class and precarious migrants were routinely required to navigate long before the pandemic (e.g., family separation, restriction of personal mobility, maintaining connection through technology). Therefore, we paid particular attention to the challenges and opportunities posed by virtual participatory video, particularly on resultant changes to attention, creativity, and relationality (core tenets of face-to-face participatory video) when time and space are, by necessity, fragmented. The fragmentation of time and space in virtual participatory video entailed a greater presence of migrant realities and demands into the method itself, perhaps most notably a tangible sense of competing demands that participants were expected to negotiate at any particular moment. Attentiveness to competing demands can be particularly valuable when working with members of communities that may experience varying forms of scarcity in relation to time or space, such as migrant domestic workers or asylum-seekers. Re-thinking fragmentation as part of the texture of virtual participatory video illustrated the durability of creativity when day-to-day realities are permitted to intrude on learning over Zoom.